Skills of Human Resources Working in the Central Public Library of Basra: A Case Study - Abdel Hamid Yassin , Nada; Judy Daoud Al-Asadi, Assist .Prof. Dr. Salman (Basra studies journal, 2022)
The research aims to identify the characteristics of human resources working in the central public library in the city of Basra and to identify the availability of skills they have: personal, leadership, objectivity, technical, technical objectivity, and the skills of helping and guiding beneficiaries. The descriptive approach (case study) was adopted to complete the research, and the questionnaire was used as a main tool for collecting data for the research, and the number of human resources that were examined reached (63) individuals. The statistical package (SPSS) program was used for the purpose of analyzing the data for the research. The research reached a number of results, including: The human resources working in the Central Public Library possess personal, leadership, and assistance and guidance skills to the beneficiaries at a very good level, while the technical skills came at a good level, as all these skills came on computational circles higher than the hypothetical mean of the research. adult (2). As for the objective skills, they were not at the required level, while their technical objective skills were weak. The research concluded with a number of recommendations, including: the need to involve all human resources in the library in intensive training courses, especially in the field of information and libraries, taking into account the development of their technical skills, and technical objectivity in accordance with the developments in the field of library work, provided that this is done by developing an action plan Periodically and allocating the administrative and financial requirements for this, provided that the relevant authorities, including information departments and libraries, associations and unions specialized in the field, and libraries, whether local, Arab or foreign, are approached.